2014
DOI: 10.1186/1756-0500-7-480
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury in a 41-year-old male treated with methylphenidate: a case report

Abstract: BackgroundElevated cardiac troponin levels are consistent with the diagnosis of an acute coronary syndrome, but may also represent adverse drug reactions. Psychostimulating drugs raise both blood pressure and heart rate, and case reports of sudden death, stroke, and myocardial infarction have led to regulatory and public concern about the cardiovascular safety of these drugs.Case presentationWe present a case where a 41-year-old Norwegian male with radiating chest pain, elevated troponins, and supraventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Owing to its various uses, there is a trend of increased methylphenidate use across all ages 2 . However, concerns of myocardial infarction following its use continue to be debated 7–9 with case reports reported for children/adolescents, 10,11 adults, 12–16 and the elderly 17 . Although the mechanism for an association has yet to be elucidated, the risk of myocardial infarction may be due to the cardiopressor dopaminergic/noradrenergic effects of methylphenidate that result in increased heart rate and blood pressure 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…Owing to its various uses, there is a trend of increased methylphenidate use across all ages 2 . However, concerns of myocardial infarction following its use continue to be debated 7–9 with case reports reported for children/adolescents, 10,11 adults, 12–16 and the elderly 17 . Although the mechanism for an association has yet to be elucidated, the risk of myocardial infarction may be due to the cardiopressor dopaminergic/noradrenergic effects of methylphenidate that result in increased heart rate and blood pressure 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that methylphenidate may induce coronary spasm, causing ST-elevation MI, reduce left ventricular function,17 cause acute MI,18 and rarely, cause pericarditis and cardiomyopathy among long-term users 19. In adults, using methylphenidate is associated with acute MI20 21 and a 1.8-fold increase in the risk of ventricular arrhythmia 13. Although MI is generally rare among children and adolescents, this has been reported in a child with ADHD with comorbid Tourette syndrome 18.…”
Section: Discussionmentioning
confidence: 97%
“…The acute coronary syndrome was ruled out by coronary angiography. Considering the mechanism of action of this medication, the authors suggested the temporary occurrence of vasoconstriction of the coronary arteries against the background of tachycardia of increased myocardial oxygen demand [94].…”
Section: Causes and Mechanisms Of Elevated Cardiac Troponins While Using Medications With Cardiotoxic Propertiesmentioning
confidence: 99%